(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2025)
Artificial Intelligence (AI) in higher education is reshaping instructional methods and academic development, especially for undergraduate library students. This study investigates the perceived impact of AI tools on the academic development of library students across 11 Nigerian universities spanning four geopolitical zones. A descriptive survey design was used; data were collected from 276 respondents using questionnaires and analyzed with SPSS. Findings reveal a high level of AI awareness (95%) and usage, with tools like ChatGPT, Google Bard, and Grammarly being the most commonly used. Students primarily employ AI for research, writing, and studying, and report improvements in assignment completion speed, content quality, and comprehension of complex topics. However, concerns remain about overdependence on AI and limited use for exam preparation. Challenges hindering effective use include high data costs, poor digital skills, unreliable internet, and power supply issues. Despite these barriers, students generally hold positive attitudes toward AI’s role in education. The study concludes that while AI presents significant opportunities to enhance academic development in Nigerian higher education, addressing infrastructural, educational, and ethical challenges is inevitable. Recommendations include training programs, infrastructural investment, policy development, and responsible AI integration strategies.